Lung ultrasound supports clinical evaluation of feeding competence development in preterm neonates - Controzzi, Tiziana; Chesi, Francesca; Scaramuzzo, Rosa Teresa; Giampietri, Matteo; Morganti, Riccardo; Fiori, Simona; Moretti, Elena; Gargani, Luna; Filippi, Luca (Frontiers in Pediatrics, 2023)
The achievement of alimentary competencies is a milestone in the development of preterm neonates. Ten percent of neonates< 37 weeks of gestational age and 25% of those VLBW experience swallowing disorders, with an increased risk of problems in the early phase of life (failure to thrive, growth retardation, inhalation, and consequent risk of pulmonary infection) and later in life due to delayed development of oromotor skills. The main diagnostic tools for swallowing disorders are endoscopic (fiber-optic endoscopic examination of swallowing, FEES) or radiographic (videofluoroscopic swallowing study, VFSS) exams. Given the invasiveness of these methods and the bias due to rheologic differences between bolus and contrast medium, FEES and VFSS are poorly reproducible. Moreover, neither of the technique is capable of detecting post-meal inhalations, especially microinhalations or those consequent to a whole meal rather than to a single swallowing. Lung ultrasound (LUS) is a widespread, repeatable, safe, fast point-of-care tool and we reported previous encouraging results in detecting silent and overt inhalation related to the meal in children with dysphagia/gastroesophageal reflux disease (GERD) risk factors. Methods: We report a pilot study, that investigated LUS approach (performing imaging before and after meals) to assess feeding competence development in a cohort of n. 19 newborns < 32 weeks of age. Results: Meal monitoring by LUS did not show any significant difference in scoring before/after eating. The achievement of full enteral feeding correlates with GA at birth (p<0.001) but not with LUS scoring. The introduction of the first meal by bottle correlates both with gestational age (p<0.001) and ultrasound scores (p=0.004). LUS score at 7 days of life resulted predictive for length of invasive/non-invasive respiratory support (p=0.002) and length of oxygen supply (p=0.001), while LUS score at 48 hours of life did not (p n.s.). Discussion: Our study suggests that the development of oral feeding skills is not strictly dependent on gestational age. Moreover, our research suggests the predominant role of LUS in predicting the time of readiness to oral feeding, as the LUS score can be a marker of respiratory and lung wellness, and consequently a predictor of neonate stability during deglutitory apnea.